IMPLEMENTASI HUKUM KELUARGA SEBAGAI REKAYASA SOSIAL MASYARAKAT DALAM UPAYA MENINGKATKAN KESADARAN HUKUM DAN KEPATUHAN HUKUM - M. Mutamakin; M Amir Mahmud (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2022)
Family law is in an important position in community life, contributing to creating and realizing an orderly and harmonious society. Family law becomes very interesting to be studied and discussed with the aim of developing human resources so that it can be reformed to family members. Thus to keep a substantive eye on the issues that occur, the legislature hopes to reform family law that can serve as a buffer in people's lives. The research focuses on family law as a form of community social engineering to build and raise legal awareness and the state must be present to provide signs of all regulations issued by it.